Assessing the quality of urban life in three neighbourhoods, Lilongwe, Malawi. Issue 3 (17th August 2021) - MacLean, Laura; Salama, Ashraf M.
Abstract : Recent literature corroborates a lack of critical engagement with contemporary east–south African cities and a scarcity of focus on the quality of urban life (QoUL) in Africa at large. Geographically situated in Malawi's capital city, Lilongwe, this study provides insights into the QoUL in three heterogenous neighbourhoods in the city from the perspective of the residents. The paper examines key indicators which impact urban life. Data are gathered through neighbourhood profiling and a residential attitude survey. It focuses on the individual resident's subjective assessment of their quality of life, and their view of four domains of urban life: namely, the physical, social, economic and well-being domains. Variances in demographic and socio-economic groups are discussed as well as the variances in QoUL found in three neighbourhoods. The results reveal that there is significant variance in the QoUL across the three neighbourhoods in Lilongwe. The study contributes to the ongoing discourse of QoUL by asserting that its underlying domains should not be viewed in isolation as they incessantly impact one another and that confronting urban challenges in this context should be considered at a neighbourhood scale.